High sensitive temperature sensor silicon-based microring resonator using the broadband input spectrum - Amiri, Iraj Sadegh; Ariannejad, Mohammad Mahdi; Daud, Suzairi; Yupapin, Preecha Promphan (Elsevier, 2018)
A sensitivity enhanced optical temperature sensor has been investigated and developed based on a silicon oxynitride (SiON) waveguide microring resonator (MRR). The broadband supercontinuum (SC) output from a fiber laser cavity is injected into the input port of the MRR, where the output was detected at the drop port of MRR. The results can be useful for the sensor-based waveguide devices, where the applications such as the temperature sensors can be realized. The temperature sensor has been fabricated in an MRR-silicon base structure. Experimental characterization of inserting the SC as input source into the MRR as the temperature sensors were carried out. The advantage of using the SC as input source is that the sensor covers a wide range of wavelengths, thus sensing the temperature changes in the wide wavelength ranges which can extend the sensing device applications. This study opens a way to apply optical sensors by using broadband SC as a source for manufacturing temperature environments sensors within the MRR waveguide structures. This will enhance the ability of the current temperature sensors to function at different and long wavelength band.